The Relationship of Family Support to the Mental Health of Postpartum Patients - Defitria Kusuma Ardani; Faizah Betty Rahayuningsih (GLOBAL HEALTH SCIENCE GROUP, 2025)
Postpartum maternal mental health is a crucial aspect that significantly affects the well-being of both mother and infant. This period is often accompanied by physical, psychological, and social changes that may lead to depression, anxiety, and stress. If left unaddressed, these problems can interfere with mother–infant bonding, the quality of childcare, and the child's overall development. Family support, particularly from husbands, parents, and other household members, plays an important protective role by helping mothers adapt to their new role, reducing the risk of psychological problems, and strengthening maternal confidence in caring for the baby. This study aims to examine the relationship between family support and postpartum maternal mental health through a systematic literature review based on the PRISMA framework, covering publications from 2020 to 2025. From an initial total of 1,435 articles, 13 met the eligibility criteria and were included in the analysis. The analysis indicates that mothers with strong family support tend to have more stable mental health, whereas insufficient support increases vulnerability to depression and anxiety. In conclusion, family support has a significant influence on maintaining maternal mental health after childbirth. Therefore, family-based interventions should become a central focus in nursing and midwifery practice to enhance the quality of life of both mothers and infants.